Application of N‐Doped MoS2 Nanocrystals for Removal of Azo Dyes in Wastewater. Issue 6 (18th April 2018) - Lu, Haijiao; Wang, Jingkang; Tian, Beiqian; Huang, Xin; Bi, Jingtao; Wang, Ting; Hao, Hongxun
Abstract: As persistent and detrimental contaminants, azo dyes are difficult to be removed from wastewater. It is a worldwide challenge to develop efficient technologies for their removal. Adsorption is widely recognized to be a practical, efficient, and low‐cost technology for removal of contaminants. Compared with various conventional adsorbents, MoS2 nanocrystals possess larger specific surface area, higher surface energy, and better adsorptive properties. Since nitrogen‐doping is a common approach for modification of materials, N‐doped MoS2 nanocrystals (NDMN) were first used as adsorbents for removal of the azo dye methyl orange. Compared with bulk MoS2 and MoS2 nanocrystals, NDMN showed much higher efficiency and reusability. This study provides inspiration for exploring and expanding the applications of NDMN. Abstract : Adsorption is widely accepted as a feasible, efficient, and low‐cost technology for removal of contaminants like azo dyes. Nitrogen‐doped MoS2 nanocrystals were applied as adsorbents for removal of the azo dye methyl orange. They exhibit great potential for elimination of such dyes in wastewater treatment and are predestined for wider applications in industrial crystallization technology.